Exploring evolutionary theories of plant defence investment using field populations of the deadly carrot. (31st October 2019) - Martinez-Swatson, Karen; Kjøller, Rasmus; Cozzi, Federico; Simonsen, Henrik Toft; Rønsted, Nina; Barnes, Christopher
Abstract: Background and Aims: There are a number of disparate models predicting variation in plant chemical defences between species, and within a single species over space and time. These can give conflicting predictions. Here we review a number of these theories, before assessing their power to predict the spatial–temporal variation of thapsigargins between and within populations of the deadly carrot ( Thapsia garganica ). By utilizing multiple models simultaneously (optimum defence theory, growth rate hypothesis, growth–differentiation balance hypothesis, intra–specific framework and resource exchange model of plant defence), we will highlight gaps in their predictions and evaluate the performance of each. Methods: Thapsigargins are potent anti-herbivore compounds that occur in limited richness across the different plant tissues of T. garganica, and therefore represent an ideal system for exploring these models. Thapsia garganica plants were collected from six locations on the island of Ibiza, Spain, and the thapsigargins quantified within reproductive, vegetative and below-ground tissues. The effects of sampling time, location, mammalian herbivory, soil nutrition and changing root-associated fungal communities on the concentrations of thapsigargins within these in situ observations were analysed, and the results were compared with our model predictions. Key Results: The models performed well in predicting the general defence strategy of T. garganica and the above-ground distribution of thapsigargins, but failed to predict the considerable proportion of defences found below ground. Models predicting variation over environmental gradients gave conflicting and less specific predictions, with intraspecific variation remaining less understood. Conclusion: Here we found that multiple models predicting the general defence strategy of plant species could likely be integrated into a single model, while also finding a clear need to better incorporate below-ground defences into models of plant chemical defences. We found that constitutive and induced thapsigargins differed in their regulation, and suggest that models predicting intraspecific defences should consider them separately. Finally, we suggest that in situ studies be supplemented with experiments in controlled environments to identify specific environmental parameters that regulate variation in defences within species.